Determinan Kinerja Keuangan Pemerintah Kabupaten/Kota di Provinsi Sumatera Selatan - Putri Meilanda; Periansya Periansya; Rosy Armaini (Syntax Corporation, 2023)
This study analyzes the determinants of financial performance in the District/City Governments of South Sumatra Province using panel data from 2017 to 2021. The independent variables examined are Regional Government Prosperity, Regional Government Size, Regional Government Dependency Level, and Capital Expenditure. The research applies the Common Effect Model (CEM) approach for panel data regression analysis. Data is sourced from local government financial reports and other statistical data. The findings reveal that Regional Government Prosperity and Regional Government Size have a significant positive impact on financial performance, while the Regional Government Dependency Level has a significant negative impact. However, Capital Expenditure does not significantly influence financial performance. Simultaneously, the variables of Regional Government Prosperity, Regional Government Size, Regional Government Dependency Level, and Capital Expenditure exert a significant influence on the financial performance of District/City Governments in South Sumatra Province.